Current State of Conservation Physiology for Amphibians: Major Research Topics and Physiological Parameters - Jun-Kyu Park; Yuno Do (Animals, 2023)
Analysis of physiological responses can be used to assess population health, identify threat factors, and understand mechanisms of stress. In addition to this, conservation physiologists have sought to establish potential management strategies for environmental change and evaluate the effectiveness of conservation efforts. From past to present, the field of conservation physiology is developing in an increasingly broader context. In this review, we aim to categorize the topics covered in conservation physiology research on amphibians and present the measured physiological parameters to provide directions for future research on conservation physiology. Physiological responses of amphibians to environmental stressors are the most studied topic, but conservation physiological studies on metamorphosis, habitat loss and fragmentation, climate change, and conservation methods are relatively lacking. A number of physiological indices have been extracted to study amphibian conservation physiology, and the indices have varying strengths of correlation with each subject. Future research directions are suggested to develop a comprehensive monitoring method for amphibians, identify interactions among various stressors, establish physiological mechanisms for environmental factors, and quantify the effects of conservation activities on amphibian physiology.